Coherent Photoproduction of Low-pT Charmonium in Peripheral Heavy Ion Collisions within the Color Dipole Model. (15th February 2022) - Yu, Gongming; Cai, Yanbing; Fu, Yongping; Yang, Haitao; Gao, Quangui; Hu, Qiang; Hu, Liyuan; Li, Wei; Song, Yushou
Abstract : We calculate the centrality dependence for coherent photoproduction of very low-p T J / ψ at Relativistic Heavy Ion Collider (RHIC) and Large Hadron Collider (LHC) energies within the impact parameter-dependent saturated color dipole model. By using the large equivalent photon fluxes, we present the differential cross-section of very low-p T J / ψ produced by coherent photonuclear in peripheral heavy ion collisions. The numerical results demonstrate that our calculation agrees with J / ψ data in peripheral heavy ion collisions at Relativistic Heavy Ion Collider (RHIC) energies.